Development of Bio-Friendly Nanomaterials and Quantum Dot-Integrated Hydrogels for Multifunctional Biomedical Applications: From Sensing to Therapeutic - Khoshbakht Marvi, Parham (My University, 2025)
The emergence of nanotechnology and biocompatible nanomaterials has given a completely new dimension to the landscape of biomedical engineering, enabling integrated platforms for diagnostics, therapy, and real-time monitoring. This thesis presents a cohesive body of work focused on the development of bio-friendly nanostructures, ranging from nanozymes to multifunctional quantum dot-based hydrogel matrices. The research trajectory commences with the design of phytochemical-assisted platinum nanozymes derived from Prunella vulgaris herbal resource, exhibiting robust peroxidase-like activity and high sensitivity in colorimetric detection of hydrogen peroxide and glutamate. These enzyme-mimicking nanoparticles demonstrated notable antioxidant activity and offered cost-effective and biocompatible solutions for biosensing applications. Building on these insights, the second phase of this work transitions toward carbon-based quantum dots (CDs) synthesized via hydrothermal treatment of the same herbal precursor. These CDs were uniformly embedded within a hydrogel matrix through in situ free radical polymerization, yielding a multifunctional composite system. The resultant hydrogel exhibited pH-responsive fluorescence across a wide range (pH 3–11), UV-blocking capability, pH-responsive sustained drug release, indirect drug release monitoring, and retained nanozymatic activity. In vitro evaluations substantiated the system’s cytocompatibility, establishing its promise as a trackable drug delivery vehicle and smart wound dressing with integrated sensing and therapeutic features. To overcome the architectural and functional constraints of the prior hydrogel systems, particularly non-linear pH-sensing profile, indirect drug monitoring, suboptimal pH-responsive release behavior during the wound healing process, and the absence of intrinsic antioxidant or antibacterial activity in CDs, a novel class of boron nitride-based carbon quantum dots (BNCQDs) was synthesized via a one-pot, polyphenol-enriched hydrothermal method. These BNCQDs, endowed with abundant surface functionalities (e.g., phenolic, carboxyl, hydroxyl, and amine groups) in tandem with inherent antibacterial and antioxidant properties, were incorporated into a photopolymerizable interpenetrating hydrogel network to expand their applications. The resulting injectable platform effectively addressed the entire aforementioned limitations. In addition, by leveraging high‑precision microscale DLP 3D printing, these hydrogels were successfully patterned into complex geometries with exceptional spatial fidelity, thereby broadening their prospects for personalized, application‑specific biomedical devices. By and large, the studies in this thesis lay the foundation for scalable, multifunctional, and bio-friendly nanocomposite platforms, bridging nanozymatic sensing and advanced regenerative therapies.